2012
DOI: 10.1039/c2cp41166k
|View full text |Cite
|
Sign up to set email alerts
|

Solid oxide fuel cells with both high voltage and power output by utilizing beneficial interfacial reaction

Abstract: An intriguing cell concept by applying proton-conducting oxide as the ionic conducting phase in the anode and taking advantage of beneficial interfacial reaction between anode and electrolyte is proposed to successfully achieve both high open circuit voltage (OCV) and power output for SOFCs with thin-film samarium doped ceria (SDC) electrolyte at temperatures higher than 600 1C. The fuel cells were fabricated by conventional route without introducing an additional processing step. A very thin and dense interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 37 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, as shown in Figure S4 of the Supporting Information, high open circuit voltages (OCVs) were obtained by the fuel cell with the Ni+BZCY anode at all temperatures, and for instance, 1.01 V at 750 °C was measured, which is much higher than 0.709 V for a cell with a Ni+SDC anode. The improved OCVs of the cell with the Ni+BZCY anode should be attributed to the beneficial reaction of BZCY and SDC to form an interfacial layer between the anode and the electrolyte …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, as shown in Figure S4 of the Supporting Information, high open circuit voltages (OCVs) were obtained by the fuel cell with the Ni+BZCY anode at all temperatures, and for instance, 1.01 V at 750 °C was measured, which is much higher than 0.709 V for a cell with a Ni+SDC anode. The improved OCVs of the cell with the Ni+BZCY anode should be attributed to the beneficial reaction of BZCY and SDC to form an interfacial layer between the anode and the electrolyte …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Su et al recently demonstrated that such proton conductors can react with doped ceria electrolytes to form an electron blocking layer over a SDC surface. As a result, the OCV of cells with thin-film SDC electrolytes was also improved . We expect that an increasing number of anodes for direct-hydrocarbon SOFCs and catalysts for the steam reforming of hydrocarbons with protonic conductors will be reported in the near future.…”
Section: Conclusion and Prospectsmentioning
confidence: 93%
“…As a result, the OCV of cells with thin-film SDC electrolytes was also improved. 413 We expect that an increasing number of anodes for direct-hydrocarbon SOFCs and catalysts for the steam reforming of hydrocarbons with protonic conductors will be reported in the near future.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…summarized some electrochemical data of typical cathodes including BSCF, La 0.625 Sr 0.375 Co 0.25 Fe 0.75 O 3 , LSM, etc., and demonstrated that the experimentally measured ASR and oxygen surface exchange rate ( k *) of perovskite cathodes are closely correlated with the theoretically calculated oxygen p-band center on the basis of density functional theory (DFT) (Figure ), which may be an appropriate descriptor for designing excellent cathode materials for SOFC. Until now, BSCF has become one of the benchmark cathode materials, which is often used as the standard cathode by researchers when developing a new fuel cell configuration or studying the anode materials. However, in terms of practical application, the activity and durability of BSCF still need to be improved, especially for durability.…”
Section: Energy Storage and Conversion Applicationsmentioning
confidence: 99%